Nitrogen Fixation in Waterlogged Paddy Soil, with Special Emphasis on Rice Straw Application - Joedoro Soedarsono; John Bako Baon (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 1981)
-